Implementation of Participatory Leadership in Class Association Management at SMPN 3 Koto XI Tarusan - Anwar, Revy; Rismawati; Gistituati, Nurhizrah; Rusdinal; Nellitawati (Jurnal Sains Sosio Humaniora, 2025)
This study examines how participatory leadership is enacted in the management of class associations at SMPN 3 Koto XI Tarusan and why this leadership approach matters for strengthening school–parent collaboration. Using a descriptive qualitative design, data were collected through in-depth interviews, participant observation, and document analysis involving the principal, homeroom teachers, class association administrators, and parents. Data were analyzed using an interactive model of data reduction, data display, and conclusion drawing, supported by triangulation to ensure trustworthiness. The findings demonstrate that participatory leadership operates through three key dimensions: shared decision-making in planning class programs, open and transparent communication between homeroom teachers and parents, and joint evaluation of class activities to support continuous improvement. These dimensions enable parents to actively participate, foster mutual trust, and enhance a collective sense of responsibility in managing class-based initiatives. The implementation of participatory leadership is supported by a culture of mutual cooperation, democratic leadership practices of homeroom teachers, and institutional support from the school, while it is constrained by limited parental availability, uneven understanding of participatory leadership principles, and socioeconomic conditions. This study highlights the practical implications of participatory leadership for school leadership by demonstrating its role in creating more inclusive, collaborative, and sustainable models of class association management. Strengthening communication strategies, clarifying organizational roles, and reinforcing institutional support are therefore essential for improving the effectiveness of school–parent partnerships.